Smoking in Moominvalley – or, Why Moominpappa and Snufkin Have Pipes - Hallila, Mika (Folia Scandinavica Posnaniensia, 2017)
The article analyzes Tove Jansson’s Moomin novels in terms of the representations of pipe smoking. The analysis focuses on three characters from the novels: Moominpappa, Snufkin, and the Joxter. The theoretic framework of the analysis is called “the semiotics of tobacco”. In this context, tobacco is regarded as a sign of the cultural sign-system, and thus what is exactly analyzed are the cultural meanings of tobacco in the Moomin novels.